2018
DOI: 10.12688/f1000research.12784.1
|View full text |Cite
|
Sign up to set email alerts
|

An overview of gambling disorder: from treatment approaches to risk factors

Abstract: Gambling disorder (GD) has been reclassified recently into the “Substance-Related and Addictive Disorders” category of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), a landmark occurrence for a behavioral addiction. GD is characterized by recurrent, maladaptive gambling behavior that results in clinically significant distress. Although the number of randomized controlled trials assessing the effectiveness of pharmacological treatments is limited, some pharmacological treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 88 publications
0
26
0
2
Order By: Relevance
“…In this profile, therefore, gambling could be a dysfunctional habit acquired and maintained over time as a mechanism to avoid problems and difficulties in emotion regulation. Thus, it could represent a group of patients more inclined to present poor response to treatment, as various studies have previously shown (3941). As such, they may require treatment programs that incorporate techniques to improve these aspects, favoring a better response to therapy (8).…”
Section: Discussionmentioning
confidence: 92%
“…In this profile, therefore, gambling could be a dysfunctional habit acquired and maintained over time as a mechanism to avoid problems and difficulties in emotion regulation. Thus, it could represent a group of patients more inclined to present poor response to treatment, as various studies have previously shown (3941). As such, they may require treatment programs that incorporate techniques to improve these aspects, favoring a better response to therapy (8).…”
Section: Discussionmentioning
confidence: 92%
“…Actually, it seems that in the community, most individuals who have had gambling problems end up recovering without having totally abstained from gambling behavior, during the process [25]. Therefore, although abstinence is the most common therapeutic goal in treatment programs [67], it could be timely to explore other alternatives such as controlled gambling, in the context of personalized therapeutic approaches, discussing with the patient their own goals and objectives [14, 68]. However, focusing on T4 and T5, it is necessary to bear in mind that other associated factors may be personality traits such as lower reward dependence and low persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic program has been described elsewhere and consists of individualized outpatient cognitive-behavioral therapy for PG, aimed at achieving abstinence from gambling. Treatment was protocolized, and the main techniques used were psychoeducation, motivational interviewing, stimulus control, cognitive restructuring and relapse prevention ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%